HUMAN RIGHTS: THE IMPORTANCE OF IMPLEMENTING AND ENFORCING HUMAN RIGHTS IN INDONESIA TODAY - Tia lahera; Dinie Anggraeni Dewi (Journal Civics And Social Studies, 2021)
There are still many human rights violations in Indonesia, starting from the lightest to the most serious in the implementation of human rights, and there is no mechanism for handling these human rights. From this research using literature review which aims to learn from existing references to understand the meaning of human rights and apply the values of Pancasila which contain the values of civilized human principles because they are the enforcement of human rights in civic life so that students can appreciate it more. the rights of everyone by not violating human rights. This human right has the power of fundamental or fundamental power. Currently, there are violation cases that have occurred because many people still do not understand the violation cases so that it is easier for people to violate the rights of others. Protection and maintenance of human rights within a national institutional framework is established in an institution such as the Indonesian Child Protection Commission (KPAI), the National Commission ini penegakan hukum hak asasi manusia dilaksanakan secara khusus melalui badan peradilan, yang Pengadilan HAM menyasar pada pengadilan HAM berat, dan yang mempunyai wewenang untuk mengetes UUD 1945 yaitu mahkamah konstitusi. Hak-hak tersebut sebagian besar ditegakkan oleh Mahkamah Konstitusi, dan banyak putusan yang melanggar hukum telah dibuat. Keputusan ini memiliki nilai strategis, sehingga dapat menjaga hak asasi warga negara.